Cultural Wisdom Meets Artificial Intelligence: A Deep Learning Based Model for Character Education Rooted in Panca Waluya - Sutisna, Ade; Nurjanah, Nunuy; Romdonah Awaliyah, Yatun; Dian Hendrayana, R. (Proceeding of International Joint Conference on UNESA, 2025)
Character education in the digital era faces growing challenges due to globalization, moral decline, and the weakening of local cultural identity among students. This study proposes a novel approach by integrating Panca Waluya, a set of five core Sundanese values: Cageur (healthy), Bageur (kind-hearted), Bener (honest), Pinter (intelligent), and Singer (skilled), with deep learning technology to strengthen character education in schools. The research develops a model using Natural Language Processing (NLP) techniques, particularly LSTM and BERT, to analyze students’ digital expressions, such as reflective writings and online communications, in order to detect character tendencies in real time. This integration enables personalized, data-driven character assessment and feedback for students and educators. By grounding AI applications in indigenous cultural wisdom, the model promotes a more contextual, culturally relevant, and adaptive approach to moral education. Preliminary findings indicate that the system enhances the visibility of character values in digital learning environments and offers a new pathway for character development that aligns with both local heritage and technological advancement. This study contributes to the field of culturally responsive pedagogy and presents a promising framework for integrating artificial intelligence into character education in the Indonesian context.